Development of the first non-hydroxamate selective HDAC6 degraders. Issue 79 (13th September 2022) - Keuler, Tim; König, Beate; Bückreiß, Nico; Kraft, Fabian B.; König, Philipp; Schäker-Hübner, Linda; Steinebach, Christian; Bendas, Gerd; Gütschow, Michael; Hansen, Finn K.
Abstract : In this study, we utilised a difluoromethyl-1, 3, 4-oxadiazole zinc-binding group to develop the first non-hydroxamate selective HDAC6 degraders (PROTACs). Abstract : The targeted degradation of histone deacetylase 6 (HDAC6) by heterobifunctional degraders constitutes a promising approach to treat HDAC6-driven diseases. Previous HDAC6 selective degraders utilised a hydroxamic acid as a zinc-binding group (ZBG) which features mutagenic and genotoxic potential. Here we report the development of a new class of selective HDAC6 degraders based on a difluoromethyl-1, 3, 4-oxadiazole warhead as ZBG.